2022
DOI: 10.2147/ijwh.s383651
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Female Stress Urinary Incontinence on Quality of Life, Mental Health, Work Limitation, and Healthcare Seeking in China, Taiwan, and South Korea (LUTS Asia): Results from a Cross-Sectional, Population-Based Study

Abstract: Background: Stress urinary incontinence (SUI) is common among adult women with negative effects on psychosocial well-being, mental health, and health-related quality of life. The purpose of the research is to determine if SUI in women is a factor implicated in changes in health-related quality of life (HRQoL) in both physical and mental health domains and in work difficulties. Methods: Data of women 40 years or older from a cross-sectional, population-based, internet survey were examined post-hoc. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…14 Similarly, a study of 4208 women aged ≥40 years conducted by Chow et al showed a significant association between SUI and work dysfunction in terms of starting working, continuing working, staying focused at work, interacting with people and completing work. 15 Regarding the potential role of comorbidities, we found that self-rated health, a comorbidity measure, 30,31 influenced the association between UI and WA, especially in SUI.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…14 Similarly, a study of 4208 women aged ≥40 years conducted by Chow et al showed a significant association between SUI and work dysfunction in terms of starting working, continuing working, staying focused at work, interacting with people and completing work. 15 Regarding the potential role of comorbidities, we found that self-rated health, a comorbidity measure, 30,31 influenced the association between UI and WA, especially in SUI.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have reported UI associating with lower education, lower occupational status and severe economic hardships 12,13 . In working life, UI has a negative impact on concentration, interaction with people, performance of physical activities, self‐confidence and the ability to complete tasks without interruption 14,15 . Regarding outcomes of work ability, a previous population‐based longitudinal cohort study of women aged 54–65 years and followed for 14 years with biennial interviews showed that urinary incontinence was associated with increased risks for work disability, 16 operationalized as experiencing impairments or health problems limiting the kind or amount of paid work one can do.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary incontinence has been shown to be associated with increased rates of depression and higher stress in women across the globe. [4][5][6] Chronic obstructive pulmonary disease (COPD) and asthma are significant causes of pulmonary morbidity. The Global Burden of Disease study reports that 212 million and 262 million people are affected by COPD and asthma, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Left untreated, SUI can have a strong impact on quality of life (QoL). Urinary incontinence has been shown to be associated with increased rates of depression and higher stress in women across the globe 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…SUI may be caused by an anatomical defect in the bladder neck, hypermobility of the urethra, or intrinsic sphincter deficiency 1 and can negatively impact quality of life, self-esteem, and social activity in women. 2 The International Consultation on Incontinence (ICS) recommends pelvic floor muscle training (PFMT) as the initial standard nonsurgical treatment for SUI. 3 Traditional conservative treatment for SUI in women involves strengthening of the pelvic floor muscles.…”
Section: Introductionmentioning
confidence: 99%